A282 EFFECTS OF BIFIDOBACTERIUM BIFIDUM IN MICE INFECTED WITH CITROBACTER RODENTIUM. (1st March 2018) - Wen, B; Taibi, A; Villa, C R; Sagaidak, S; Lee, S; Comelli, E
Abstract: Background: Various strains of Bifidobacterium bifidum are probiotics with beneficial properties in intestinal inflammation, including pathogen infection. B . bifidum strain MIMBb75 (BB75) sustains intestinal homeostasis and mitigates intestinal discomfort in patients with irritable bowel syndrome. Citrobacter rodentium is a murine pathogen causing transmissible colonic hyperplasia and colitis with pathogenicity similar to foodborne enterohaemorrhagic Escherichia coli O157:H7 in humans and with features of inflammatory bowel disease. Aims: This study aimed to examine if oral administration of B. bifidum MIMBb75 attenuates pathology associated with C. rodentium infection. Methods: C57Bl6/J male mice were randomized into 4 groups; groups 1 and 2 received BB75 daily (10 9 CFU/ml in 200 µl PBS by gavage) starting 7 days before (group 1), or on the same day (group 2) as C. rodentium infection (10 9 CFU/ml in 100 µl LB-culture); groups 3 and 4 received sterile PBS and served as infection (group 3) and sham (group 4) controls. Mice were sacrificed at day 10 post-infection (p.i.). Fecal C. rodentium and B. bifidum load were assessed by culturing and qPCR, respectively. Crypt hyperplasia and intestinal inflammation were assessed by histology. Barrier integrity was evaluated by pathogen translocation to secondary organs and in vivo permeability test. Results: C. rodentium infection resulted in colonic hyperplasia, inflammation and barrier dysfunction. Fecal C. rodentium viable count increased and reached a plateau (10 10 CFU/g of feces) at day 10 p.i., with clearance on day 24 p.i., regardless of probiotic treatment (p>0.05). B. bifidum administration resulted in 10 7 cells/g of feces, with no effect of timing of administration (p>0.05). Though, B. bifidum treatment did not attenuate crypt hyperplasia nor inflammation associated with the infection (p>0.05). Conclusions: These data suggest that C. rodentium and B. bifidum can co-exist in the gut with no mutual displacement; this is in line with research showing that BB75 is well equipped for gut colonization. However, in this experimental setting, BB75 cannot counteract C. rodentium pathology. Findings from this study may provide insights for the understanding of probiotics behavior and their clinical relevance in intestinal inflammation. Funding Agencies: NSERC and JP Bickell Foundation to Elena M Comelli; NSERC Alexander Graham Bell Canada Graduate Scholarship to Bijun Wen.